Midostaurin: a magic bullet that blocks mast cell expansion and activation - Valent, Peter; Reiter, Andreas (Annals of oncology, 2020)
Abstract. Clinically relevant features in patients with systemic mastocytosis (SM) include the cosmetic burden of lesional skin, mediator-related symptoms, and
Gesehen am 28.08.2018
Available online 6 January 2020